Belief-neutral efficiency in financial markets - Patrick Beißner; Frank Riedel (Bielefeld University, Center for Mathematical Economics (IMW), 2025)
Heterogeneous beliefs among market participants can lead to questionable speculative trading that goes beyond any risk-sharing motives. We demonstrate that such unwarranted betting behavior in market equilibrium can be mitigated by introducing nonlinear pricing for ambiguous contracts, without compromising legitimate risk-hedging activities. While Arrow-Debreu equilibria generally fail to achieve belief-neutral efficiency, we establish a modified version of the first welfare theorem in which equilibria with nonlinear prices uphold belief-neutral efficiency. Moreover, we show that belief-neutral efficiency can be ensured by introducing suitable transaction costs for ambiguous financial assets.
urn:nbn:de:0070-pub-30010868
Keywords: D81; C61; G11; 330; Belief-Neutral Pareto efficiency; Heterogeneous Beliefs; Knightian Uncertainty; Ambiguity; General Equilibrium